2022
DOI: 10.3390/ijerph191710975
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Response to OnabotulinumtoxinA: Different Definitions, Different Predictors

Abstract: The identification of patients who can benefit the most from the available preventive treatments is important in chronic migraine. We explored the rate of excellent responders to onabotulinumtoxinA in a multicenter European study and explored the predictors of such response, according to different definitions. A pooled analysis on chronic migraineurs treated with onabotulinumtoxinA and followed-up for, at least, 9 months was performed. Excellent responders were defined either as patients with a ≥75% decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
9
1
1
Order By: Relevance
“…The decrease of more than 30% in the number of days with headache after the first month with ONA treatment indicates that ONA treatment can be successful [ 27 ]. The decrease in monthly headache days in ONA treatment is more than 75% between the beginning and the next application shows that the response to the treatment is excellent [ 52 ]. Ornello et al reported those who responded to a reduction in headache days after ONA application at 3, 6 and 9 months [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of more than 30% in the number of days with headache after the first month with ONA treatment indicates that ONA treatment can be successful [ 27 ]. The decrease in monthly headache days in ONA treatment is more than 75% between the beginning and the next application shows that the response to the treatment is excellent [ 52 ]. Ornello et al reported those who responded to a reduction in headache days after ONA application at 3, 6 and 9 months [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in monthly headache days in ONA treatment is more than 75% between the beginning and the next application shows that the response to the treatment is excellent [ 52 ]. Ornello et al reported those who responded to a reduction in headache days after ONA application at 3, 6 and 9 months [ 52 ]. In the results at 3 months, the rate of excellent responders to ONA treatment was 8.6% ( n = 248/2879).…”
Section: Discussionmentioning
confidence: 99%
“…Several real-world studies have been published, with findings consistent with PREEMPT studies in CM patients with and without MOH [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Real-world studies primarily exploring the effectiveness and safety of BT-A compared to the baseline are summarized in Table 2 .…”
Section: Clinical Use Of Bt-a In the Treatment Of Chronic Migrainementioning
confidence: 99%
“…Gender does not influence patients’ response to BT-A [ 124 ]. Additionally, BT-A may also be a safe and valuable tool to treat CM in the elderly, when many treatments are not indicated [ 126 ].…”
Section: Clinical Use Of Bt-a In the Treatment Of Chronic Migrainementioning
confidence: 99%
See 1 more Smart Citation